2007
DOI: 10.1001/archotol.133.10.1031
|View full text |Cite
|
Sign up to set email alerts
|

Amplification and Overexpression of HER2/neu Gene and HER2/neu Protein in Salivary Duct Carcinoma of the Parotid Gland

Abstract: Objectives: To detect amplification of the HER2/neu gene by means of fluorescence in situ hybridization (FISH) in a series of 13 salivary duct carcinomas (SDCs) and to compare the results with immunohistochemical (IHC) assessment of HER2/neu protein expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 30 publications
(48 reference statements)
4
67
0
Order By: Relevance
“…Due to the limited efficacy and severe complications of surgery and radiotherapy, a more systematic therapeutic approach should be analyzed in order to improve the prognosis of SDC. The present study demonstrated a high positivity rate for HER-2/neu and AR expression in SDC, indicating that SDC carcinogenesis may resemble that of breast ductal carcinoma or prostate cancer (4,7,11,13,15,18,21,22). As HER-2/neu blockers (trastuzumab) are effective in treating HER-2-overexpressing breast cancer, this agent may be useful for the treatment of SDC.…”
Section: A B C D Esupporting
confidence: 50%
See 1 more Smart Citation
“…Due to the limited efficacy and severe complications of surgery and radiotherapy, a more systematic therapeutic approach should be analyzed in order to improve the prognosis of SDC. The present study demonstrated a high positivity rate for HER-2/neu and AR expression in SDC, indicating that SDC carcinogenesis may resemble that of breast ductal carcinoma or prostate cancer (4,7,11,13,15,18,21,22). As HER-2/neu blockers (trastuzumab) are effective in treating HER-2-overexpressing breast cancer, this agent may be useful for the treatment of SDC.…”
Section: A B C D Esupporting
confidence: 50%
“…Due to the rarity of SDC, little data regarding its clinicopathological characteristics exists. The standard treatment for SDC is surgery in combination with radiotherapy, however, the prognosis of SDC is poor (4)(5)(6)(7). Effective therapeutic strategies rely on a sufficient understanding of SDC and its prognostic factors, therefore, the aim of the present retrospective study was to summarize the clinicopathological characteristics of SDC and to evaluate the current treatment modalities currently used at the Affiliated Hospital of Stomatology of Nanjing University (Nanjing, Jiangsu, China).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of HER2 contributes to the pathogenesis of many cancers including breast, ovarian, gastric, and salivary gland cancers [111][112][113][114]. Stephens et al reported mutations in ERBB2 kinase domain in 4% of the tumor samples from patients with lung cancer [115].…”
Section: Erbb2mentioning
confidence: 99%
“…erbB receptors, especially of erbB2, play an important role in carcinoma formation, and its dysfunction promotes tumourigenesis. Overexpression of the erbB2 gene was frequently observed in human tumours, including those of breast, lung, stomach, and oral cavity (25)(26)(27). Capable of stable and highly specific silencing of gene expression, siRNAs have been extensively applied to silence abnormal gene expression in the treatment of cancer (28).…”
Section: Discussionmentioning
confidence: 99%